Synthesis, Structure, Photoluminescence, and Optical Properties of (Co/B) Co-Doped ZnO Nanoparticles - Arda, L.; Veziroglu, S.; Ozdogan, K.; Ozugurlu, E. (WILEY-V C H VERLAG GMBH, 2024)
Co/B co-doped ZnO nanoparticles, denoted as Zn0.95-xBxCo0.05O, are synthesized using the sol-gel method to explore the effects of the defects on optical properties. The stoichiometry is adjusted by varying the doping levels (x = 0.00, 0.01, 0.02, 0.03, 0.04, and 0.05). X-ray diffraction is employed to analyze the structural characteristics of all Co/B co-doped ZnO nanoparticles, confirming the presence of a hexagonal Wurtzite structure by assessing the c/a ratios. To investigate structural defects, photoluminescence properties are measured using the Fluorescence Spectrophotometer, revealing violet, blue, green, and red emissions. With the doped of boron (B), a shift from green emission to blue emission occurs, indicating a transformation of singly charged oxygen vacancies (V-O(+)) to V-Zn vacancies. Fourier Transform Infrared (FTIR) spectra (4000-400 cm(-1)) are acquired using the Perkin Elmer Spectrum Two FTIR-ATR spectrophotometer. The surface morphology, crystallite size, and nanoparticle shapes are characterized through Transmission Electron Microscope (TEM) analysis. Elemental compositions are determined using Electron Dispersive Spectroscopy (EDAX). The Shimadzu 2600 UV-Spectrophotometer is used to examine optical characteristics. The samples' energy band gaps are calculated, and the impact of dopant elements on these optical characteristics is examined. Five different models are used to compute the refractive index.
Keywords: energy gap; nanoparticles; photoluminescence; refractive index; zinc oxide; REFRACTIVE-INDEX; MAGNETIC-PROPERTIES; ENERGY-GAP; EMISSION; FILMS; Chemistry; Science & Technology - Other Topics; Materials Science